2014
DOI: 10.1007/s13277-014-2599-0
|View full text |Cite
|
Sign up to set email alerts
|

LAPTM4B-35 protein as a potential therapeutic target in gastric cancer

Abstract: The objective of this study is to investigate lysosome-associated protein transmembrane 4b-35 (LAPTM4B-35) protein expression in gastric cancer and its clinical implications. LAPTM4B-35 protein expression in 652 gastric cancer specimens and matched adjacent non-cancerous tissues was evaluated by immunohistochemical staining. Subsequently, the relationship between LAPTM4B-35 protein expression, clinical pathological parameters, and prognosis of gastric cancer was determined. LAPTM4B-35 protein expression was si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 12 publications
1
11
0
Order By: Relevance
“…A similar result was detected by Xiao et al, (2013), who reported that LAPTM4B was activated and overexpressed in serum of BC patients. Moreover, other studies have demonstrated that LAPTM4B has been upregulated in many human cancers, such as lung cancer (Tang et al, 2014), gastric cancer (Zhang et al 2014), and prostate cancer (Zhang et al, 2015), and is known to have a role as a dynamic cancer-associated biomarker that is involved in several biological processes (Kasper et al, 2005). We observed significant increases in both RANKL and OPG serum levels in the MBC group compared with the control and NMBC groups.…”
Section: Correlation Between the Studied Biomarkers And Clinical Datasupporting
confidence: 50%
“…A similar result was detected by Xiao et al, (2013), who reported that LAPTM4B was activated and overexpressed in serum of BC patients. Moreover, other studies have demonstrated that LAPTM4B has been upregulated in many human cancers, such as lung cancer (Tang et al, 2014), gastric cancer (Zhang et al 2014), and prostate cancer (Zhang et al, 2015), and is known to have a role as a dynamic cancer-associated biomarker that is involved in several biological processes (Kasper et al, 2005). We observed significant increases in both RANKL and OPG serum levels in the MBC group compared with the control and NMBC groups.…”
Section: Correlation Between the Studied Biomarkers And Clinical Datasupporting
confidence: 50%
“…LAPTM4B, an oncogene, is highly expressed in many solid tumors and inversely associated with overall survival and disease-free survival of patients with breast cancer [31], gastric cancer [32], gallbladder cancer [33], HCC [34], ovarian cancer [35] and cervical cancer [36]. Moreover, the polymorphism region in the 5ʹ-UTR of …”
Section: Discussionmentioning
confidence: 99%
“…It could promote the proliferation of tumor cells, boost invasion and metastasis, resist apoptosis, initiate autophagy and assist drug resistance [4]. In addition, overexpression of LAPTM4B was significantly correlated with poor prognosis in breast cancer [5], gallbladder cancer [6,7], ovarian cancer [8], HCC [9][10][11], gastric cancer [12] and cervical cancer [13] LAPTM4B gene has two alleles named LAPTM4B*1 and LAPTM4B*2 (GenBank numbers AY219176 and AY219177, respectively). Allele *1 contains only one copy of a 19-bp sequence at the 5'UTR in the first exon, whereas the sequence in allele *2 is duplicated and tandemly repeated [14].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that LAPTM4B-35 activity was elevated in various malignant tumors, which was associated with poor prognosis [46]. Moreover, it was indicated that LAPTM4B could increase the proliferation and metastasis of tumor cells, reduce apoptosis, and assist drug resistance, which involved in activated PI3K/AKT and Ras-MAPK signaling pathways [7].…”
Section: Introductionmentioning
confidence: 99%